2023
DOI: 10.34133/bdr.0013
|View full text |Cite
|
Sign up to set email alerts
|

Plant Promoters and Terminators for High-Precision Bioengineering

Abstract: High-precision bioengineering and synthetic biology require fine-tuning gene expression at both transcriptional and posttranscriptional levels. Gene transcription is tightly regulated by promoters and terminators. Promoters determine the timing, tissues and cells, and levels of the expression of genes. Terminators mediate transcription termination of genes and affect mRNA levels posttranscriptionally, e.g., the 3′-end processing, stability, translation efficiency, and nuclear to cytoplasmic export of mRNAs. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 194 publications
0
3
0
Order By: Relevance
“…The properties of synthetic promoters and their applications have been described in several review articles [256][257][258][259][260][261]. However, research in this field is progressing rapidly, fueled by climate change, decreasing arable land area, and a fast-growing global population [1].…”
Section: Discussionmentioning
confidence: 99%
“…The properties of synthetic promoters and their applications have been described in several review articles [256][257][258][259][260][261]. However, research in this field is progressing rapidly, fueled by climate change, decreasing arable land area, and a fast-growing global population [1].…”
Section: Discussionmentioning
confidence: 99%
“…The properties of synthetic promoters and their applications were described in several review articles [252][253][254][255][256][257]. However, research in this field is progressing rapidly, fueled by progressing climate changes, decreasing arable land area, and a fast-growing global population [1].…”
Section: Discussionmentioning
confidence: 99%
“…This may be because variations in the TATA box can affect binding of RNA Polymerase II to the core promoter region that drives not only basal gene expression but also environmentdependent gene expression (Grace et al, 2004). The TATA box, identified by its consensus sequence of eight base pairs, "TATA(A/T)A(A/T)(A/G)," typically resides between 30 and 70 base pairs upstream from the transcription start site in plant promoters (Brooks et al, 2023) but some studies identified the 13 bp TCACTATATATAG as the consensus sequence in promoters of highly expressed plant genes (Kiran et al, 2006). These GC-rich TATA extension sequences that flank the TATA motif are thought to govern the formation of alternative transcriptional complexes needed in different physiological settings and alter the rate and stability of TATA binding protein and TFIIB transcription factor binding to the TATA box to recruit RNA Polymerase II (Wolner and Gralla, 2001;Kiran et al, 2006;Shi and Zhou, 2006).…”
Section: Known Nodulation Genes Included (Associated Traits)mentioning
confidence: 99%